Efektifitas dan Efisiensi Penggunaan Klorinator sebagai Sarana Pelarut Disinfektan di Usaha Kecil dan Menengah (UKM) - Nur Ahmad Habibi; Citra Tristi Utami; Mulyana Mulyana; Ratu Ruri Amelia (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2019)
Water is an important substances in the food industry. The quality of water that is used in the small Industry (UKM) generally has bad quality. This is caused by lack of knowledge and cost. The aim of the study was to evaluate effectiveness and efficiency of using chlorinator as disinfectan (chlorine) solvent in the small industry (UKM). This study used complete randomized design with 2 repetitions and analyzed water quality before and after treatment. The parameters that was used was coliform and eschericia coli (e. coli) contaminant and total chlorine in the water. The cost efficiency was calculated with evaluate chlorine/m3. Results showed a decrease of coliform and E.coli (p<0.05), from 2,3 x105 cfu/100 ml to 0 cfu/ml for both. Furthermore, total chlorine after treatment showed no decrease significantly (p<0.05). The cost efficiency of using chlorinator was cheap, just Rp. 916/m3. The use of chlorinator was effective to decrease total microbiology contaminant and can keep total chlorine concentration in the standard of water quality for hygiene and sanitation. Furthermore, chlorinator was also efficience in cost to be implemented in small industry (UKM)